Smoking - Charlis, Anne (Wayland Hove, 1991)
Smoking by Anne Charlish provides an insightful look into the dangers and consequences of tobacco use. The book offers a clear explanation of the addictive nature of smoking and the harmful effects it has on health, both in the short and long term. Charlish covers the societal impact of smoking, exploring its role in public health issues and the global efforts to reduce smoking rates. It also delves into the various prevention and cessation methods available, making it a valuable resource for individuals, educators, and policymakers interested in understanding and combating smoking-related harm.